Multimedia: The News Agency In Promoting Journalistic Experiences - Martins Barbosa Couto, Daniela; de Oliveira, Luana Natacha; de Souza Rezende, Júlia; Lopes, Paulo Sérgio; Andrade, Amanda; dos Santos Souza, Emanuela (Guará Journal, 2019)
The Multimedia News Agency is linked to the Journalism program at UEMG - Divinópolis campus and emerged as a proposal and a means for conceptual and practical experiences to take place. In 2016, it began its activities through the extension project "Multimedia: the news agency in the promotion of journalistic experiences," recognized by the Internal Program for the Promotion of Research and Extension (Proinpe) at the Divinópolis campus. At the interface between theoretical discussion and practice, the News Agency serves as a space for extension, experimentation, and experience.